Fine liquid-core polymer fibers for microhydraulic applications: A versatile process design. (October 2022) - Hufenus, Rudolf; Hofmann, Jonas; Gooneie, Ali
Graphical abstract: Highlights: A liquid core is continuously fed into a microscale polymer fiber during melt-spinning. Different liquid-polymer combinations can be developed by the unique co-extrusion process. Computational fluid dynamics calculations confirm the versatility of the process for a wide range of microfluidic conditions. Liquid-core fibers show impressive pressure transfer properties, promising for microhydraulic applications. Abstract: Miniaturization is an essential requirement to advance areas where conventional mechatronic systems may struggle. Microhydraulic devices that combine resilience and compliance could thus revolutionize microrobot applications like locomotion and manipulation. Spurred by the deformability and structural stability provided by veins in insect wings, microscale liquid-core fibers were created, comprising of a polymeric sheath and a liquid core. A microfluidic co-extrusion spinneret was designed, assisted by computational fluid dynamics studies, to achieve such unique liquid-core fibers. Hydraulic pressure transfer tests were successfully applied on fine, up to 10 m long, oil-filled polyamide fibers. The results showed a pressure transfer with a fiber length-dependent delay of ∼ 20–100 s for fiber lengths of ∼ 1–10 m, and a viscoelastic behavior with relaxation times that behave linearly with fiber length. These findings enable the development of resilient and deformable microhydraulic systems within restricted available space, predestined for applications in soft robotics.